(untitled) (Journal of EAHIL, 2021)
Preserving the history of medicine is an important task for health sciences librarians. In this regard, the provision of special collections can play a significative role. This article presents the initiative of the University of Rome Campus Bio-Medico Library (UCBML) in creating valuable sources for the history of medicine through the establishment of several special collections. The aim of this article is to highlight the importance of special collections to promote issues relating to the field of medical history.